Regression analysis of caterpillar 793D haul truck engine failure data and through-life diagnostic information using the proportional hazards model - Carstens, Wiehahn Alwyn (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScEng)--Stellenbosch University, 2012.